The Fixator—A simple method for mounting of arthropod specimens and photography of complex structures in liquid - Wanke, Dominic; Bigalk, Sonia; Krogmann, Lars; Wendt, Ingo; Rajaei, Hossein (Zootaxa, 2019)
Mounting and preparing arthropods in liquids for photography and further investigations is a challenging task and may lead to unsatisfactory results and, in the worst case, to damage to specimens. A new method is presented here, which allows the fixation of specimens of different sizes under various degrees of pressure. The method is illustrated by three case studies from different groups of insects and arachnids.